Results of NCCTG N0275 (Alliance) – a phase II trial evaluating resection followed by adjuvant radiation therapy for patients with desmoplastic melanoma. (1st July 2016) - Rule, William G.; Allred, Jacob B.; Pockaj, Barbara A.; Markovic, Svetomir N.; DiCaudo, David J.; Erickson, Lori A.; Deming, Richard L.; Schild, Steven E.
Abstract: To examine, in a prospective fashion, the utilization and efficacy of adjuvant radiation therapy (RT) in patients with resected desmoplastic melanoma (DM). Adult patients with resected, margin‐negative, and nonmetastatic DM were eligible for this single‐arm prospective phase II study. Patients were to receive postoperative RT, 30 Gy in five fractions, to the operative bed with 2‐ to 3‐cm margins (depending on the tumor location). Nodal basin RT was not allowed. The primary study endpoint was the 2‐year local recurrence rate (LRR). Secondary endpoints included the incidence of regional and distant metastatic disease, progression‐free survival, overall survival (OS), and treatment‐related toxicity. Twenty patients with a single de novo DM lesion meeting trial eligibility criteria were enrolled and treated. The 2‐year LRR was 10%, with two patients demonstrating a LR within 2 years of completion of protocol therapy. No regional or distant failures occurred. OS at 2 and 5 years was 95 and 77%, respectively. There were no grade 3 or higher acute or late adverse events that were related to the protocol therapy. Adjuvant RT after wide local excision (WLE) for DM is efficacious and well tolerated. It should be considered for DM patients after margin‐negative WLE. Additional study is needed to further refine low‐risk patient populations that can potentially have adjuvant RT omitted as part of the treatment plan. Abstract : This prospective trial examines the efficacy of adjuvant radiation therapy in patients with resected desmoplastic melanoma.